Synthesis, characterization and biological activity of new azo coumarin compounds - Saeed, Yousif Ismael (2018)
The development of new heterocyclic based azo dye derivatives is becoming the significant attraction of medicinal chemists. Azo compounds consist of at least a conjugated chromophore azo (-N=N-) group in connection with one or more aromatic or heterocyclic systems. Finding that bacterial and fungal resistance and toxicity of drugs, there is a focus on the insistent need to discover new antibiotics to inhibit these human pathogenic infections. Therefore, there is an urgent need to design and develop new drugs by synthesis of analogues and modifications in existing compounds. For this purpose a new, 2-hydroxy-5-(aryl) diazenyl) benzaldehyde was obtained by the diazotization of different aromatic amines followed by coupling with salicylaldehyde, which is generally carried out at a low temperature. The new prepared compounds were reacted with ethylacetoacetate in the presence of piperidine and glacial acetic acid as catalyst via Knovenagel condensation to form new azo coumarin compounds. The structures of all the newly synthesized compounds have been characterized and confirmed by TLC and spectroscopic methods, such as FTIR, 1H-NMR, 13C-NMR and mass spectrometric analysis. Subsequently, the bioactivity evaluation was done for all synthesized drugs against different human pathogenic infections, such as two gram-positive bacteria (Staphylococcus aureus S273, Bacillus subtilis B29) and two gram-negative bacteria (Escherichia coli E266, Acinetobacter anitratus A9) with one fungal strain (Aspergillus brilliance ATCC 16404). Furthermore, from the investigation of antimicrobial screening data it is clearly evident that most of the synthesized compounds exhibited significant to moderate antibacterial activity against tested microorganisms as compared to the standard drugs, whereas, some of them exhibited weak activity. Among all the new compounds tested 2-hydroxy-5- ((mercapto-1,3,4- thiadiazol-2-yl diazenyl) benzaldehyde, 3-acetyl-6-((5-mercapto-1,3,4-thiadiazol-2- yl) diazenyl)-2H-chrome-2-one and 2-hydroxy-5-((2,4- dinitrophenyl) diazenyl) benzaldehyde were more potent as compared to the standard drug streptomycin. In addition, 2-hydroxy-5-((2,4-dinitrophenyl) diazenyl) benzaldehyde exhibited moderate potency against the tested fungus compared to nystatin. In general, the synthesized compounds were active against all bacteria strains and exhibited greater activity compared with the standard drug. Finally, it was concluded that the newly synthesized compounds were able to inhibit the growth of certain microbes, which were successfully characterized, and in vitro antimicrobial activities were explored so that they may be used for drug developments in the future.